Prostate Imaging and Reporting and Data System Version 2.1: Limitations for Clinical Use - Byung Kwan Park (Journal of Urologic Oncology)
The Prostate Imaging and Reporting and Data System version 2.1 (PI-RADSv2.1) is commonly utilized in interpreting magnetic resonance imaging (MRI) scans in men with elevated prostate-specific antigen levels. This system aids in the risk stratification of prostate cancer and facilitates communication between radiologists and urologists. However, the current PI-RADSv2.1 decision rules present several pitfalls, particularly in relation to definitions, categorizations, MRI sequences, MRI protocols, and MRI interpretations. There are few reports addressing these limitations. The aim of this review is to outline the pitfalls encountered when applying PI-RADSv2.1.